2017
DOI: 10.1007/s00404-017-4396-7
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and its relation with medical nutrition therapy in gestational diabetes

Abstract: Medical nutrition therapy was associated with reduction of the fetal weight in women with GDM and the weight decreases with length of treatment. Birth weight above 4 kg was as prominent in the non-diabetic women as in the women with GDM without MNT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…According to a WHO report [14], high-risk women who follow lifestyle change interventions (both diet and exercise) reduce the risk of excessive GWG, thereby reducing risk of perinatal complications. In a study by Vestgaard et al [15], there was relatively lower mean birth weight in newborns of GDM mothers on extended-duration MNT as compared to non-GDM women or GDM women who had no MNT. Birth weight above 4 kg was seen in 18% of MNT-treated GDM women versus 27 and 24% ( p = 0.012) in non-diabetic and no MNT GDM women, respectively.…”
Section: Gwg and Energy Intakementioning
confidence: 99%
“…According to a WHO report [14], high-risk women who follow lifestyle change interventions (both diet and exercise) reduce the risk of excessive GWG, thereby reducing risk of perinatal complications. In a study by Vestgaard et al [15], there was relatively lower mean birth weight in newborns of GDM mothers on extended-duration MNT as compared to non-GDM women or GDM women who had no MNT. Birth weight above 4 kg was seen in 18% of MNT-treated GDM women versus 27 and 24% ( p = 0.012) in non-diabetic and no MNT GDM women, respectively.…”
Section: Gwg and Energy Intakementioning
confidence: 99%
“…They demonstrated that the fetal macrosomia rate was 4. 3% in the intervention group compared to 13.1% in the control group (3).…”
Section: Introductionmentioning
confidence: 79%
“…Physical activity of moderate intensity should be maintained and carried out constantly, but adapted to the evolution of the pregnancy. In combination with nutritional intervention, physical activity appears to be more effective for gestational diabetes management than gestational diabetes prevention (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations